Implementation of Project-Based Learning in Morphology Learning Assessment on Morphological and Morphophonemic Process Materials - Indrayanti, Tri; Sumarwati, Sumarwati; Setiawan, Budhi; Suhita, Raheni (Universitas Pahlawan Tuanku Tambusai, 2026)
Morphology learning in higher education is important to improve students' understanding in determining words and correct word formation. This study aims to describe the application of Project-based learning in morphology learning, material on morphological and morphophonemic processes in texts. The method used is descriptive qualitative which combines classroom observation methods and document analysis of learning outcomes. The research participants were 15 students from the Indonesian Language Education Study Program, Universitas PGRI Adi Buana Surabaya, class of 2024, selected through a purposive sampling method. The project type was to identify morphological and morphophonemic processes in texts. The assessment used was a scored process assessment with criteria. The results of the study indicate that student learning outcomes using Project-Based Learning (PjBL) are successful, this can be seen in the student's score. The use of Project-Based Learning is effective in this learning because students will contribute to each other in analyzing texts that undergo morphological and morphophonemic processes. Based on these findings, it can be suggested that the use of Project-Based Learning is effective but does not rule out the possibility of using more diverse, interactive, and fun methods. The results of this study provide an important contribution in improving learning outcomes using Project-Based Learning (PjBL).